THE UNHEARD HAZARD: A REVIEW OF HIGH-LEVEL NOISE EXPOSURE AND HEARING LOSS IN THE GLOBAL ELECTRICAL POWER INDUSTRY - Abdulelah, Haider; Abdulelah, Zainab (Journal for Technology and Science, 2025)
Objective: The global electrical power generation, transmission, and distribution sector is a critical backbone of modern society, yet occupational noise exposure remains an underestimated risk that can cause permanent, irreversible, but preventable Noise-Induced Hearing Loss (NIHL). Method: This manuscript provides a comprehensive review of the effects of high-level noise on workers within electricity organizations worldwide by analyzing primary noise-generating equipment and processes from a materials science perspective, detailing pathophysiological mechanisms of NIHL, and discussing audiological and psychosocial consequences. Result: The review synthesizes global epidemiological data on hearing loss within the sector, highlighting disparities between developed and developing nations, and evaluates current noise control strategies such as the hierarchy of controls, the role of Personal Protective Equipment (PPE), and emerging materials and technologies for creating quieter electrical infrastructure. Novelty: The conclusion underscores the critical need to integrate hearing conservation programs with material design and operational management, offering a new perspective that connects occupational health with technological innovation in order to safeguard the long-term health of the global electrical workforce.